A Robust Watermarking Method Based on RDWT-DCT-SVD in the YCbCr Color Space - Son, Vu Tuan; Duc, Tong Minh (Journal of Science and Technology on Information security, 2024)
In digital copyright protection, watermarking plays a crucial role, particularly in ensuring the watermark remains imperceptible, robust against attacks, and has a high embedding capacity. The new method proposed in this paper utilizes Redundant Discrete Wavelet Transform (RDWT), Discrete Cosine Transform (DCT), and Singular Value Decomposition (SVD) to embed the watermark into a color image. Instead of using traditional methods, this approach calculates the Bhattacharyya distance between the original image and the watermark to determine the embedding factor automatically. The watermark is hidden in the Cb channel of the YCbCr color space, which minimizes the impact on the original image quality and enhances both the imperceptibility and robustness of the watermark. Experimental results show that this method not only preserves the original image quality but also withstands various types of attacks, ensuring the watermark retains its integrity and high recoverability.